PeSTZ1 confers salt stress tolerance by scavenging the accumulation of ROS through regulating the expression of PeZAT12 and PeAPX2 in Populus. (27th April 2020) - He, Fang; Niu, Meng-Xue; Feng, Cong-Hua; Li, Hui-Guang; Su, Yanyan; Su, Wan-Long; Pang, Hongguang; Yang, Yanli; Yu, Xiao; Wang, Hou-Ling; Wang, Jie; Liu, Chao; et al.
Abstract: ZINC FINGER OF ARABIDOPSIS THALIANA12 (ZAT12) plays an important role in stress responses, but the transcriptional regulation of ZAT12 in response to abiotic stress remains unclear. In this study, we confirmed that a SALT TOLERANCE ZINC FINGER1 transcription factor from Populus euphratica ( PeSTZ1 ) could regulate the expression of PeZAT12 by dual-luciferase reporter (DLR) assay and electrophoretic mobility shift assay. The expression of PeSTZ1 was rapidly induced by NaCl and hydrogen peroxide (H2 O2 ) treatments. Overexpressing PeSTZ1 in poplar 84K ( Populus alba × Populus glandulosa ) plant was endowed with a strong tolerance to salt stress. Under salt stress, transgenic poplar exhibited higher expression levels of PeZAT12 and accumulated a larger amount of antioxidant than the wild-type plants. Meanwhile, ASCORBATE PEROXIDASE2 ( PeAPX2 ) can be activated by PeZAT12 and PeSTZ1, promoting the accumulation of cytosolic ascorbate peroxidase (APX) to scavenge reactive oxygen species (ROS) under salt stress. This new regulatory model ( PeSTZ1–PeZAT12–PeAPX2 ) was found in poplar, providing a new idea and insight for the interpretation of poplar resistance. Transgenic poplar reduced the accumulation of ROS, restrained the degradation of chlorophyll and guaranteed the photosynthesis and electron transport system. On the other hand, transgenic poplar slickly adjusted K + /Na + homeostasis to alleviate salt toxicity in photosynthetic organs of plants under salt stress and then increased biomass accumulation. In summary, PeSTZ1 confers salt stress tolerance by scavenging the accumulation of ROS through regulating the expression of PeZAT12 and PeAPX2 in poplar.